Predictors of falls in recreational snowboard jumping: An observational study - Kurpiers, N.; McAlpine, P.; Kersting, U. G. (Injury, 2017)
Purpose: Jumping is popular in the sport of snowboarding. Epidemiological research has shown an increased risk of injury associated with this activity. Falls are common when jumping and although there is a logical connection between falling and injury occurrence, thus far little attention has been given to factors involved in the jumping-fall relationship. The current study aimed to add to the current knowledge base by identifying predictors of falling during intentional snowboard jumping within terrain park facilities. Methods: Seven hundred and four jumps were video recorded and qualitatively coded using a custom template of predetermined parameters related to manoeuvre choice, landing technique and jump success. Results: Falling was common within the sample population at a rate of one fall for every five jump attempts. Landings made on the flat or knuckle of the snow jump as well as incorrect board positioning at landing were found to be significant predictors of falling. Additionally the choice of manoeuvre was found to influence the risk of falls, with spinning jumps associated with a greater fall risk when compared to non spinning jumps. No clear relationship was identified between jump length measures and falling risk. Conclusion: It is likely that jumping will remain popular in snowboarding and thus research efforts should focus on minimising the risk of injury associated with this skill. Reducing the overall incidence of falling, identified in the current study to be high, is a potential area for improvement. The potential for fall risk reduction through technique and decision making changes provides justification for further research in this area.